EVALUATION OF THE AESTHETIC COMPONENT OF THE PERFORMANCE SKILL OF CHILDERS IN GROUP EXERCISES - Pozdeeva E.A.; Ovsyannikova M.A.; Korichko Yu.V.; Korichko A.A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the aesthetic indicators of performance skills in cheer sports and clarify the judge’s assessment. Methods and structure of the study. The study analyzes in detail the criteria for refereeing in cheer sports (judging provisions in the competition rules and protocols); identified single indicators of performance skills (on the example of group exercises); the most significant aesthetic indicators of the performance skills of cheerleaders were identified. To solve problems, the following methods were used: analysis and synthesis, abstraction and concretization, analysis of scientific and methodological literature, rules and protocols of competitions; questioning; mathematical methods. Results and conclusions. An analysis of the refereeing system in Russia for this sport showed the need to improve methods for evaluating group exercises. The paper presents a way to objectify refereeing in chir sports - the introduction of three teams of judges: performance, synchronism, choreography.